Transferring flood waters underground builds community climate resilience in India - CGIAR Initiative on NEXUS Gains (CGIAR System Organization, 2024)
IWMI began piloting underground transfer of floods for irrigation (UTFI) in a village in the Ganges Basin in 2015. Since then, UTFI has been recognized as an important part of the solution to two crises facing India: destructive floods and recurring water shortages. The CGIAR Initiative on NEXUS Gains is now supporting the government to better implement a national water conservation program. As a result, UTFI ponds and recharge wells have been constructed in hundreds more villages, increasing water availability by up to 8 percent to date and strengthening climate resilience.